Alternative food matrices for snack formulations in terms of acrylamide formation and mitigation. (11th October 2018) - Mesías, Marta; Delgado‐Andrade, Cristina; Morales, Francisco J
Abstract: BACKGROUND: The salty snack market is re‐inventing itself trying to offer to consumers healthier and added‐value products often based on alternative vegetables/cereals, such as vegetable chips. New options mostly involve a nutritional improvement but the toxicological aspects of the reformulation are not usually examined. This work evaluated the acrylamide formation and effectiveness of different mitigation strategies in potato chips and in alternative snacks, such as carrot and pumpkin chips. Fresh potato, carrot and pumpkin samples were fried under controlled conditions and after being subjected to different operations (soaking in water at different times/temperatures, adding lemon or vinegar as pH modifiers or salt). RESULTS: Acrylamide values in control samples of carrot (224 ± 47 µg kg −1 ) and pumpkin (514 ± 83 µg kg −1 ) were significantly lower than in the potato chip samples (3887 ± 509 µg kg −1 ). The different mitigation treatments had effects on potato and pumpkin chips, the most effective strategies being soaking options and the decrease of the pH of the medium. However, such treatments were not as effective in carrot chips. CONCLUSIONS: These new vegetable snacks could be a healthy alternative both at nutritional and toxicological level. In addition, acrylamide concentration could even be reduced with simple mitigation operations before frying. © 2018 Society of Chemical Industry